Editorial - Mensah Danquah, Monica (Ghana Library Journal, 2025)
I am delighted to present Volume 30, Issue 1 of the Ghana Library Journal . We thank all our contributors, reviewers, and the entire Editorial Board members for their support of the Ghana Library Journal. We open this edition with a timely commentary from Oppong Bekoe and colleagues, who provide a candid account of the operational, technical, and institutional challenges faced by academic journal editors in Ghana. Their reflections serve not only as a mirror of our context but also as a call to action for sustained investment in editorial infrastructure and professional development. The subsequent articles each explore critical dimensions of digital transformation and inclusive information service delivery. Arkorful and co-authors shed light on the disparities in computer literacy among distance learners in Ghana, highlighting the digital divide that continues to hinder equitable academic engagement. Their recommendations underscore the need for comprehensive digital skills development policies, particularly for underserved student populations. From Nigeria, Ogunbodede and Achugbue explore the adoption of open textbooks among undergraduate LIS students. Their study, grounded in the Diffusion of Innovations theory, demonstrates the potential of open educational resources to democratize learningprovided that awareness and institutional support are amplified.